Carbon Sequestration: Organic Carbon Stock in the Soils along with Elevation Gradient under Different Land Uses in Uttarakhand State - Gupta, M. K.; Panwar, Vijender Pal; Kumar, Manoj (Indian Forester, 2018)
Temperate climate favours organic carbon accumulation in soils and a major concern for such regions is the change that may take place in the large SOC stocks as temperatures rise. Information related to SOC stock along with elevation in Himalayan region are very scanty. Therefore, this study was conducted to estimate the SOC stock at different altitudes in various land uses viz. forests having Shorea robusta (sal), Pinus roxburghii (chir), Quercus leucotrichophora (banj oak), Cedrus deodara (deodar), Pinus wallichiana (kail), Picea smithiana and Abies pindrow (silver fir and spruce) and miscellaneous; horticulture land use having Psidium guajava (Guava), Litchi chinensis (litchi), Pyrus malus (apple), Citrus spp. and Mangifera indica (mango); block plantations land use having Populus deltoides, Eucalyptus spp., Pinus roxburghii (chir), Dalbergia sissoo (shisham), Tectona grandis (teak) and Cypress cashmeriana and (Kashmir cypress) grasslands. All the thirteen districts of Uttarakhand were selected for collecting the soil samples. Under natural forest covers SOC stock increased with increasing elevation. Elevation was having significant positive correlation with SOC stock under the forests with correlation coefficient 0.950 under the horticulture land use (0.952*) under grassland ; ; (0.955*) and under plantation (0.860*) Results of one - way ANOVA indicates that SOC stock between the groups. (elevations) were significantly different at 0.05 level (Variance ratio, F = 9.955; p < 0.05) when all the vegetations were integrated and SOC stock was worked out altitude wise irrespective of vegetation in Uttarakhand, maximum SOC stock was found above 2501 m elevation (138.37 Mg ha-1) followed by the soils at elevation in between 2001 - 2500 m (115.00 Mg ha-1), 83.10 Mg ha-1 in the soils having elevation in between 1501 - 2000 m, 58.31 Mg ha-1 in between 1001 - 1500 m, 55.90 Mg ha-1 in between 501 - 1000 m and the least SOC stock 41.73 Mg ha-1 was found at less than 500 m elevation.